Bus fleet management on NTU campus : optimization and improvement of fleet size routing and scheduling - Dong Kun (2012)
This report describes the NTU shuttle bus network problems through the data collection analysis, site observation integrated with some approaches from other researchers. Firstly, through the correct surveying method selection, author can get reliable passenger loading profile and trend of passenger behaviour. Secondly, by analysing data and deriving algorithm, proposes an optimized fleet size, bus schedule and corresponding relationship between the operational cost and frequency. With the relationship, a better cost efficiency can be achieved by reducing the number of bus stops so that fulfilling the optimization of bus network. Lastly, A special discussion section is presented to solve the overloading situation appeared in shuttle bus route D, and totally 4 different solutions are proposed including application of the concept of queuing model, synchronization incorporated with actual situation, for example, synchronize the bus schedule to train arriving time. Through the analysis, a travelling time algorithm will be derived, and the solution with least total travelling time to the destination or cost will be discussed.